Microplastics in the Southern Brazilian estuary : Interactions between environment, morphology, and seasonal variation - Fonseca, Vanessa F.; Gomes, Raimara S.; Bertoldi, Crislaine F. ; 0000-0001-6156-3139; Passos, Camila C.; Semensatto, Décio; Fernandes, Andreia N. (Regional Studies in Marine Science, 2025)
Estuaries are complex environments rich in biodiversity, making it challenging to understand the distribution and occurrence of microplastics due to the multiple variables that can influence the movement of these particles. Based on this, this study evaluated the influence of different environmental aspects on the distribution and transport of microplastics in the surface waters of the Tramandaí River estuary. An average occurrence of 14.21 ± 3.07 items L−1 was identified, with a predominance of white/transparent fibers smaller than 500 µm in size. PE and PP were the predominant polymers with an average carbonyl index (CI) of 0.77 ± 0.41. From the results, it was observed that periods with little rainfall can decrease the occurrence of microplastics in the surface water of the studied estuary but increase the predominance of white or colorless particles and fragments. Additionally, anthropogenic activity and water depth influenced the occurrence and form of particles in the surface waters. Furthermore, the progressive approach to the sea decreased the occurrence of blue microplastics and increased the abundance of smaller particles. Finally, the change in tides directly impacted only the estuary point, influencing the occurrence and shape of the particles. Thus, the results demonstrated that several factors interfered with the abundance and characteristics of the microplastics found in the Tramandaí River basin. The estuary point was influenced by the largest number of variables, highlighting the complexity of these environments. Additionally, the importance of evaluating not only aspects intrinsic to the sampling site but also seasonal factors was emphasized.
Keywords: Characterization; Distribution; Estuary; Microplastics; Surface water